EFEKTIFITAS PEMBINAAN MADRASAH DINIYAH DI KOTA YOGYAKARTA - Abdul Muin (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
The issue in this research is the effectiveness of coaching committed by the Ministry of Religion of Yogyakarta to improve teaching skills of madrasah diniyah teachers. To that end, this study aims to describe the effectiveness of coaching to improve madrasah diniyah teachers’ skills and abilities. This study uses descriptive qualitative method with primary data collection through focus group discussions (FGDs), in-depth interviews, and observation while secondary is data obtained through documentation. The study showed that the Ministry of Religious Yogyakarta City officials have not been effective to guide the improvement of capabilities of madrasah diniyah teachers’ teaching skills because the Ministry of Religious Affairs has not programmed ability and teaching skills development of teachers with adequate budget.